2023
DOI: 10.1101/2023.11.28.569028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A deep lung cell atlas reveals cytokine-mediated lineage switching of a rare cell progenitor of the human airway epithelium

Avinash Waghray,
Isha Monga,
Brian Lin
et al.

Abstract: The human airway contains specialized rare epithelial cells whose roles in respiratory disease are not well understood. Ionocytes express the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR), while chemosensory tuft cells express asthma-associated alarmins. However, surprisingly, exceedingly few mature tuft cells have been identified in human lung cell atlases despite the ready identification of rare ionocytes and neuroendocrine cells. To identify human rare cell progenitors and define their lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…However, lineage-tracing studies are needed to confirm this lineage relationship between tuft cells and PNECs. In a preprint, Waghray et al (2023 preprint) described an equivalent progenitor population found in the large airways of human adults through deep scRNA-seq ( Waghray et al, 2023 preprint ). Leveraging human ALI cultures, this replicative rare cell progenitor population was shown to have the potential to differentiate into either mature tuft cells or ionocytes and was therefore termed tuft-ionocyte progenitor (TIP) cell.…”
Section: Model Systems For Studying the Human Airway Epithelium And P...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, lineage-tracing studies are needed to confirm this lineage relationship between tuft cells and PNECs. In a preprint, Waghray et al (2023 preprint) described an equivalent progenitor population found in the large airways of human adults through deep scRNA-seq ( Waghray et al, 2023 preprint ). Leveraging human ALI cultures, this replicative rare cell progenitor population was shown to have the potential to differentiate into either mature tuft cells or ionocytes and was therefore termed tuft-ionocyte progenitor (TIP) cell.…”
Section: Model Systems For Studying the Human Airway Epithelium And P...mentioning
confidence: 99%
“…The authors did not find any evidence that TIP cells could give rise to PNECs. Intriguingly, they showed that cytokines associated with asthma and CF altered the differentiation of TIP cells ( Waghray et al, 2023 preprint ). Perhaps in the context of other human respiratory diseases, TIP cells could be pathologically redirected to produce PNECs.…”
Section: Model Systems For Studying the Human Airway Epithelium And P...mentioning
confidence: 99%